2012
DOI: 10.3174/ajnr.a3327
|View full text |Cite
|
Sign up to set email alerts
|

Improved Conspicuity and Delineation of High-Grade Primary and Metastatic Brain Tumors Using “Restriction Spectrum Imaging”: Quantitative Comparison with High B-Value DWI and ADC

Abstract: Background and Purpose Restriction spectrum imaging (RSI) is a sensitive DWI technique for probing separable water diffusion compartments in tissues. Here, we evaluate RSI tumor cellularity maps (RSI-CM) derived from the spherically-restricted water compartment for improved tumor conspicuity and delineation from non-tumor tissue and reduced sensitivity to edema compared with high b-value DWI and ADC. Materials and Methods RSI was performed in 10 pre-surgical patients: 4 with glioblastoma, 3 with primary CNS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
120
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(123 citation statements)
references
References 23 publications
3
120
0
Order By: Relevance
“…The RSI design matrix includes a distribution (or “spectrum”) of effective diffusion pools spanning hindered and restricted length scales with both isotropic and anisotropic geometries. In Fig 4 we illustrate both a schematic for the RSI spectrum model and the resultant fit of the model to data collected in a 51 year-old patient with right frontal GBM prior to surgical intervention (47). Note the separation of diffusion components in different tissue types, with the primary lesion exhibiting a large volume fraction of spherically-restricted water likely stemming from water trapped within cancer cells.…”
Section: Principles Of Diffusion Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…The RSI design matrix includes a distribution (or “spectrum”) of effective diffusion pools spanning hindered and restricted length scales with both isotropic and anisotropic geometries. In Fig 4 we illustrate both a schematic for the RSI spectrum model and the resultant fit of the model to data collected in a 51 year-old patient with right frontal GBM prior to surgical intervention (47). Note the separation of diffusion components in different tissue types, with the primary lesion exhibiting a large volume fraction of spherically-restricted water likely stemming from water trapped within cancer cells.…”
Section: Principles Of Diffusion Mrimentioning
confidence: 99%
“…Also note the large fraction of free and hindered water in areas of necrosis and edema. The volume fraction of spherically restricted water (either with or without additional filtering of white matter signal using a technique called “beamforming” (48)) has been coined the RSI cellularity index or cellularity map (47, 4951). In addition, the signal from the restricted anisotropic component can be use to map the density and orientation of surrounding white matter tracts (50).…”
Section: Principles Of Diffusion Mrimentioning
confidence: 99%
“…These limitations have resulted in a surge of more advanced imaging biomarkers aimed at predicting response to therapy, as summarized in various review articles. 7,8 Among these new imaging biomarkers showing promise are diffusion MR imaging techniques, [9][10][11][12][13][14][15][16][17][18] including ADC histogram analysis. Previous results have shown that pretreatment ADC histogram analysis performed within the contrast-enhancing tumor regions can stratify patients with recurrent GBM into high-and low-risk groups.…”
mentioning
confidence: 99%
“…Moreover, pulse sequences such as RSI may allow standardization of diffusion imaging across scanners, which is currently lacking. When RSI was applied to diagnosis of brain tumors, the tumor signal was enhanced by 10-fold over conventional diffusion imaging 45 . Preliminary studies indicate that RSI may also be of great value in prostate cancer 44 .…”
Section: Targeting Approaches: Urology Vs Radiologymentioning
confidence: 99%